"Picasso in The Metropolitan Museum of Art": An Investigation of Materials and Techniques. Issue 3 (August 2013) - Arslanoglu, Julie; Centeno, Silvia A.; Digney-Peer, Shawn; Duvernois, Isabelle
Abstract : The 2010 exhibition " Picasso in The Metropolitan Museum of Art " presented the unparalleled opportunity to examine the working methods and materials of Pablo Picasso's paintings in the museum's collection, 34 works in total, covering a span of over 60 years. All paintings were comprehensively examined and studied using infrared reflectography and x-ray radiography. The paintings with paint surfaces that visually presented qualities associated with alkyd, enamel, or house paints were analyzed. Four paintings presenting such significant characteristics emerged from the group and are the focus of this study. Pigment and binding media analyses indicated the possible use of non-traditional artist's paints but not necessarily house, alkyd, or enamel paints. Picasso's infinite creativity was reflected in his experimental nature with materials. Specifically, his manipulation and alteration of the oil medium, which directly impacted the appearance and handling properties of the paint, must be taken into account. Ultimately, the results of this study illustrate the difficulty in identifying house, boat, or other non-traditional artist's paints by visual examination alone and the challenges of their analytical characterization. Our analyses showed the presence of traditional artist's materials of the time period but did not definitively identify chemical markers of house or other non-traditional artist's paints.